United States : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for United States. (IMF Staff Country Reports; Country Report, 2020)
The U.S. is in the midst of an unprecedented social and economic shock. The longest expansion in U.S. history has been derailed by the unanticipated advent of COVID-19. To preserve lives and support public health, it was necessary to put in place a broad-based shutdown of the U.S. economy in March. Despite the gradual easing of state lockdown restrictions and lifting of stay-at-home orders starting in late April, the collateral economic damage has been enormous. First, and foremost, as of July 16, more than 136,000 Americans have tragically lost their lives and many more have become seriously illustrations Almost fifteen million Americans have lost their jobs, many small and large businesses are under financial stress, and future prospects are highly uncertain. Reopening decisions will have to be handled carefully to mitigate the economic costs while containing the ongoing rise in COVID-19 infection rates. It will likely take a prolonged period to repair the economy and to return activity to pre-pandemic levels. All in all, globally there will be difficult months and years ahead and it is of particular concern that the number of COVID-19 cases in the U.S. is still rising.